مساهمة في دراسة تقنية بسيطة لتنقية المياه في التجمعات الصغيرة والمناطق المعزولة باستخدام مواد طبيعية - إلهام منير بدور (Tishreen University, 2019)
Water purification in small communities and isolated areas using natural materials is preferred because of their relative simplicity, cost and efficiency. Based on the above, we studied providing drinking water in small communities and isolated areas; water purification using natural materials, the research has addressed the study of purification of water used for drinking in those areas; where samples of natural water were collected from various sources of different rejoins, dams, springs and rivers, processed with the powder of Moringa seeds, in addition to the development of the purification process by adding sand to obtain drinking water when chlorine is used which react with organic matter present in the water which cause cancer to humans. The research concluded that water needs to be treated in the most appropriate and feasible manner that meets quality requirements clean water free from contaminants, decomposed organic matter and nutrients such as nitrogen and phosphorus before sterilized with chlorine so as not to interact with it and cause damage to the public health of water consumers. تبقى عملية تنقية المياه في التجمعات الصغيرة والمناطق المعزولة باستخدام مواد طبيعية مُفضّلة بسبب بساطتها النسبية، وكلفتها المناسبة، وفعاليتها الجيدة. انطلاقاً مما سبق قمنا بدراسة تأمين مياه صالحة للشرب في التجمعات الصغيرة والمناطق المعزولة وذلك بتنقية المياه باستخدام مواد طبيعية، فقد تطرق البحث لدراسة تنقية المياه المستخدمة للشرب في تلك المناطق؛ حيث أُخذت عينات من مياه طبيعية من مصادر مختلفة من مناطق وسدود و ينابيع و أنهار مختلفة و تمت معالجتها باستخدام مسحوق بذور نبات المورينجا، إضافة لتطوير عملية التنقية بإضافة الرمل بهدف الحصول على مياه صالحة للشرب وذلك عند لزوم استخدام الكلور الذي يتفاعل مع المواد العضوية الموجودة في المياه والتي تسبب السرطانات للإنسان. و توصل البحث إلى ضرورة معالجة المياه بالطريقة الأنسب وذات الجدوى والتي تحقق شروط جودة المياه الصالحة للشرب الخالية من الملوثات والمواد العضوية المنحلة والمغذيات مثل النتروجين و الفوسفور قبل تعقيمها بالكلور كي لا تتفاعل معه و تسبب الأضرار على الصحة العامة لمستهلكي المياه.